2012
DOI: 10.5336/medsci.2011-24415
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pupil Diameters of Emmetropes and Myopes under Photopic, Mesopic and Scotopic Conditions, Using the Infrared Pupillometer Integrated Within Schwind Sirius Multifunctional Diagnostic Device

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : To assess the pupil diameters of emmetropes and myopes in photopic, mesopic and scotopic conditions. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Pupil diameters of 49 emmetropic subjects [spherical equivalent (SE) values ±0.25 diopter (D) with a mean age of 31.0±10.5 years (range 17 to 58 years)], and 61 agematched (mean age 31.3±8.9 years, range 17 to 52 years) myopic subjects were measured with the infrared pupillometer integrated withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Bootsma et al [19] noticed that digital binocular IR pupillometry is superior for obtaining standardized measurements of pupil size, because it is much more closer to real-life conditions. Some features of Procyon and Sirius IR pupillometer are similar in terms of binocularity, objectivity, standardization of illumination and dynamic measuring [21]. Altan et al [25] concluded that the tendency of smaller pupil size measurements with the Ocular Wavefront Analyzer might be due to the slightly higher ambiance illumination or an effect of accomodative miosis when subjects fixated on the a red light-emitting diode target in this device.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bootsma et al [19] noticed that digital binocular IR pupillometry is superior for obtaining standardized measurements of pupil size, because it is much more closer to real-life conditions. Some features of Procyon and Sirius IR pupillometer are similar in terms of binocularity, objectivity, standardization of illumination and dynamic measuring [21]. Altan et al [25] concluded that the tendency of smaller pupil size measurements with the Ocular Wavefront Analyzer might be due to the slightly higher ambiance illumination or an effect of accomodative miosis when subjects fixated on the a red light-emitting diode target in this device.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this will be the first study that evaluates the pupil measurements of patients with PXS using IR pupillometer integrated within CSO Sirius Corneal Topographer, since the Pub-Med search and other literature researches did not reveal any other similar papers. The majority of articles compared various pupillometers using different techniques and devices [12,[14][15][16][17][18][19][20][21][22][23][24][25]. The digital pupillometers allow examination of the dynamic pupil function in addition to scotopic, mesopic and photopic measurements of pupil size and provide objective data using a computer software.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,11,12,13,14,15,16,17,18,19,20 There is a growing interest in diagnosis in these areas, and our custom-made pupillometer may be useful as an easily-applicable, non-invasive diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…The potential value of PLR evaluations in normal and disease conditions have been investigated in many studies in areas such as the autonomic nervous system, cognitive function, drug metabolism, pain response, psychology, fatigue, and sleep disorders. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 There is a growing interest in diagnosis in these areas, and our custom-made pupillometer may be useful as an easily-applicable, non-invasive diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%